PENGARUH PENGALAMAN ORGANISASI, PENGALAMAN MAGANG, DAN SELF EFFICACY TERHADAP KESIAPAN KERJA MAHASISWA TINGKAT AKHIR - Erlangga, Fendry; Bakti, Dadang Karya; Aprilani, Deddy (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2024)
This research examines the influence of organizational experience, internship experience and self-efficacy on work readiness of final year students at the Faculty of Social and Political Sciences, University of Lampung. Using a quantitative approach, data was obtained through an online survey distributed via social media, with a sample consisting of 96 respondents from final year students at the Faculty of Social and Political Sciences, University of Lampung who had organizational experience and internship experience. Data analysis was carried out using SPSS. The results of the research show that organizational experience, internship experience and self-efficacy have a partially positive and significant influence on the work readiness of final year students at the Faculty of Social and Political Sciences, University of Lampung. Meanwhile, simultaneously there is an influence between all variables.